Electrochemical behavior of AISI 1020 steel in type C commercial gasolines - Marinho Fonseca, Rafaela (Array, 2019)
In the present paper, the corrosion behavior of 1020 carbon steel in commercial gasoline-ethanol blends was investigated. The composition of each gasoline-ethanol blend was evaluated by infrared spectroscopy, and the ethanol content was determined by the ABNT 13992 reference method. Electrochemical Impedance Spectroscopy (EIS) and polarization methods were employed to evaluate corrosion resistance and penetration rates. Statistical analyses revealed that the gasoline’s solution resistance governs the corrosion process, the RON (Research Octane Number) and MON (Motor Octane Number) numbers as well as the olefin content being more related to the corrosion rates. The polarization resistance had minor impact on the corrosion process.